1985
DOI: 10.1093/carcin/6.12.1761
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of benzo[a]pyrene by cultured rat and human buccal mucosa cells

Abstract: Primary cultures of epithelial and fibroblast cells derived from human oral mucosa were studied for the ability to activate a tobacco smoke carcinogen, benzo[a]pyrene (BP). The cells were exposed to benzo[a]pyrene for 18 h. The cell-free medium was extracted with ethylacetate/acetone, and high-pressure liquid chromatography analysis of this fraction revealed that BP tetrols and diols were the major metabolites formed by both epithelial and fibroblast cells. However, the epithelial cells had a much higher rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Other studies have also reported that buccal epithelial cells in vitro exhibit active metabolism of tobacco smoke constituents, such as nicotine-derived nitrosamine ketone [i.e. 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone] and benzo[a]pyrene (Autrup et al, 1985; Liu et al, 1993). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported that buccal epithelial cells in vitro exhibit active metabolism of tobacco smoke constituents, such as nicotine-derived nitrosamine ketone [i.e. 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone] and benzo[a]pyrene (Autrup et al, 1985; Liu et al, 1993). …”
Section: Discussionmentioning
confidence: 99%
“…Oral mucosal cells are the first barrier for inhalation or ingestion route and are capable of metabolizing proximate carcinogens to reactive products. [3][4][5][6] Approximately, 90% of human cancers originate from oral epithelial cells. [7] They represent a preferred target site for early genotoxic events induced by carcinogenic agents entering the body through inhalation and ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Detoxification enzymes play variable roles in oral cancer development as implied from several studies. Expression of mRNA for various CYPs 5,6 and metabolism of the polycyclic aromatic hydrocarbon benzo(a)pyrene to DNA binding intermediates 7 in cultured human NOK indicate existence of oxidative metabolism. Moreover, both normal and transformed keratinocyte lines significantly oxidize specific CYP substrates, e.g., ethoxyresorufin and the tobacco-specific carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, known to undergo metabolism by several CYPs.…”
mentioning
confidence: 99%